THE EFFECT OF ENGLISH INPUT ON YOUNG LEARNERS’ PRONUNCIATION PERFORMANCE USING EMERSION PROGRAM - Khosiyono, Banun Havifah Cahyo (Universitas Muria Kudus, 2022)
There is no dearth of studies on pronunciation problems of EFL learners; however, research on pronunciation problems of young learners is scarce. Therefore, to fill this research gap, the present quasi-experimental study aimed at investigating the effect of L2 input on pronunciation performance of young learners in English. To this end, two groups of primary school learners were recruited as the study participants. Both groups were of the same age (10 years of age), and they were all native speakers. Group A’s exposure to English was rather restricted since education was exclusively in English while Group B received a great deal of input through an Immersion Program. Data were collected by means of a pictorial pronunciation test. The analysis of the data shows that Group B participants far outperformed Group A students. Everything being equal, this could be interpreted as the result of greater exposure Group B participants had to English through the immersion program they were following. Thus, it can be concluded that by increasing the amount of learners’ input language acquisition, in general, and pronunciation performance, in particular, can be facilitated.